An item response theory approach to constructing and evaluating brief and in‐depth financial literacy scales. Issue 3 (11th July 2020) - Ranyard, Rob; McNair, Simon; Nicolini, Gianni; Duxbury, Darren
Abstract: We applied item response theory (IRT) to construct and evaluate new brief and in‐depth financial literacy scales. A survey of a UK adult sample ( N = 589) included 50 questions to assess knowledge about managing financial resources and competence in using personal finance‐related information—including five widely used items, on interest rates, inflation, investment diversification, mortgages and bonds. IRT applied to a scale of these items identified some limitations, overcome via further iterations to construct a new brief scale with sound psychometric properties. IRT was then applied iteratively to our pool, resulting in an in‐depth, 20‐item scale, also psychometrically sound, covering four broad financial domains: everyday money transactions; the concept of money; borrowing; and saving and investment. Parallel 10‐item sub‐scales were also evaluated. The validity of the new scales was demonstrated by regression analyses which found that, controlling for demographic variables, financial literacy predicted key indicators of financial well‐being.